Different shades of green? Unpacking habitual and occasional pro-environmental behavior. (November 2015) - Lavelle, Mary Jo; Rau, Henrike; Fahy, Frances
Highlights: This research deployed an innovative tool to investigate habitual and occasional pro-environmental behavior. The paper dismantled the notion of pro-environmental behavior as a single entity. Profiles differed for 'green' acting persons for occasional and habitual behaviors. Once-off activities disproportionately benefit higher income households. Abstract: This paper argues for a disaggregation of pro-environmental behavior into habitual and occasional behavior. The former captures routine everyday activities such as regularly buying organic food or habitually conserving water. The latter describes occasional or once-off activities such as installing insulation and purchasing energy-efficient household appliances. Drawing on a survey of 1500 households in the Republic of Ireland and Northern Ireland that developed both behavioral and attitudinal indices to investigate household consumption, we group respondents according to their scoring on each index. Results show that the socio-demographic and attitudinal profiles of households that report habitual pro-environmental behavior differ significantly from those that engage in once-off actions. This clearly impacts on environmental and sustainability policy, most notably the financial incentivization of sustainable consumption. Moreover, significant social sustainability issues arise, with rewards for once-off activities disproportionately benefiting better-off households while those who engage in routine pro-environmental behavior tend to face higher costs.